Grand Canyon country : its majesty and its lore - Fishbein, Seymour L. (National Geographic park profiles, 1997)
A first-person narrative takes readers to the Grand Canyon, describing its awe-inspiring sunsets, hikes on steep and treacherous trails, and other sights.